Development of a 3D virtual environment as a support tool for tourism diffusion of the archaeological site of Teotihuacan - Amador Reyes, Juan de Jesús; Zuñiga Ortega, Jorge Alfonso; Mejía Buñuelos, Christian; Morales Ramírez, Alejandra; Mota Hernández, Cinthya Ivonne (Acta Universitaria, 2014)
The use of new technologies is going through a considerable increase in recent years. The reason of promoting the development and application of these systems in different areas is to achieve a benefit for the users which manifests in any aspect of their lives. This project presents a virtual reality system based on 3D environments which main objective is being a support tool for the tourism diffusion of the archaeological site of Teotihuacan and also a new way to visit and walk around the site simulating the reality through a virtual tour.
Keywords: Array; Array; Array; Array